Genome-wide identification and expression analysis of two-component system genes in sweet potato (Ipomoea batatas L.) - Huo, Ruxue; Zhao, Yanshu; Liu, Tianxu; Xu, Meng; Wang, Xiaohua; Xu, Ping; Dai, Shengjie; Cui, Xiaoyu; Han, Yonghua; Liu, Zhenning; Li, Zongyun (Frontiers in Plant Science, 2023)
Two-component system (TCS), which comprises histidine kinases (HKs), histidine phosphotransfer proteins (HPs), and response regulators (RRs), plays essential roles in regulating plant growth, development, and response to various environmental stimuli. TCS genes have been comprehensively identified in various plants, while studies on the genome-wide identification and analysis of TCS in sweet potato were still limited. Therefore, in this study, a total of 90 TCS members consisting of 20 HK(L)s, 11 HPs, and 59 RRs were identified in the genome of Ipomoea batatas. Furthermore, their gene structures, conserved domains, and phylogenetic relationships were analyzed in detail. Additionally, the gene expression profiles in various organs were analyzed, and response patterns to adverse environmental stresses were investigated. The results showed that these 90 TCS genes were mapped on 15 chromosomes with a notably uneven distribution, and the expansion of TCS genes in sweet potato was attributed to both segmental and tandem duplications. The majority of the TCS genes showed distinct organ-specific expression profiles, especially in three types of roots (stem roots, fibrous roots, tuberous roots). Moreover, most of the TCS genes were either induced or suppressed upon treatment with abiotic stresses (drought, salinity, cold, heat) and exogenous phytohormone abscisic acid (ABA). In addition, the yeast-two hybrid system was used to reveal the HK-HP-RR protein-protein interactions. IbHP1, IbHP2, IbHP4, and IbHP5 could interact with three HKs (IbHK1a, IbHK1b, and IbHK5), and also interact with majority of the type-B RRs (IbRR20–IbRR28), while no interaction affinity was detected for IbHP3. Our systematic analyses could provide insights into the characterization of the TCS genes, and further the development of functional studies in sweet potato.